2005
DOI: 10.1063/1.1935042
|View full text |Cite
|
Sign up to set email alerts
|

Environment of hafnium and silicon in Hf-based dielectric films: An atomistic study by x-ray absorption spectroscopy and x-ray diffraction

Abstract: The atomic structure of HfSiO and HfSiON was investigated before and after thermal annealing using x-ray diffraction and x-ray absorption spectroscopy. In HfSiO, the Hf atoms are arranged in a monoclinic HfO 2 structure with Hf as second nearest neighbors, while Si is in a SiO 2 environment. Thermal annealing induces crystallization of HfSiO with subtle changes in Hf-Hf distances. In the case of HfSiON, a stable structure is observed around the Hf atoms, which remains unaffected after annealing. Nitrogen is pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
10
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 19 publications
4
10
0
1
Order By: Relevance
“…It is well established that amorphousness is highly desirable in high-K gate oxide materials for their application in metal-oxide semiconductor devices since the absence of grain boundaries in amorphous materials prevents the leakage current. Increase in crystallization temperature has also been reported by Morais et al 7 for reactively sputtered HfSiO films deposited from a HfSi target. Afify et al 4,5 have reported an enhancement of crystallization temperature upto 1060°C for HfO 2 -SiO 2 powder prepared by sol-gel technique, while Neumayer and Cartier 6 have reported a crystalliastion temperature of 1000°C for spin coated HfO 2 -SiO 2 composite films.…”
Section: Introductionsupporting
confidence: 71%
“…It is well established that amorphousness is highly desirable in high-K gate oxide materials for their application in metal-oxide semiconductor devices since the absence of grain boundaries in amorphous materials prevents the leakage current. Increase in crystallization temperature has also been reported by Morais et al 7 for reactively sputtered HfSiO films deposited from a HfSi target. Afify et al 4,5 have reported an enhancement of crystallization temperature upto 1060°C for HfO 2 -SiO 2 powder prepared by sol-gel technique, while Neumayer and Cartier 6 have reported a crystalliastion temperature of 1000°C for spin coated HfO 2 -SiO 2 composite films.…”
Section: Introductionsupporting
confidence: 71%
“…It is confirmed, by a comparison with La capped HfSiON and HfSiO, that nitrogen has a role to prevent La from diffusion into the high-k whereby an interaction of La with HfSiON/SiO 2 is less than that with HfSiO/SiO 2 [17]. Thus, nitrogen incorporation is believed to improve the thermodynamic stability [18].…”
Section: Role Of Nitrogenmentioning
confidence: 50%
“…Under ambient conditions, the radius of Hf 4+ ion is not suitable to take tetrahedral coordination with O 2− ion and the Hf 4+ ion tends to form higher coordination polyhedra [23]. The recent studies by EXAFS [24,25] and ab initio MD calculation [26] indicate that the HfO m polyhedron is highly distorted and coordination number around Hf atom in amorphous hafnium silicate is around 6 to 8. Three types of oxygen coordinate can be available in the film; (1) non-bridged oxygen (NBO) of SiO 4 tetrahedra, (2) bridged oxygen (BO) of cross-linked SiO 4 tetrahedra (-Si-O-Si-) and (3) terminal OH group (tOH).…”
Section: Resultsmentioning
confidence: 97%